Clinical Outcomes of Incidental Venous Thromboembolism in Cancer and Noncancer Patients: The SWIss Venous ThromboEmbolism Registry (SWIVTER) - Spirk, David; Sebastian, Tim; Barco, Stefano; Banyai, Martin; Beer, Jürg H.; Mazzolai, Lucia; Baldi, Thomas; Aujesky, Drahomir; Hayoz, Daniel; Engelberger, Rolf P.; Kaeslin, Thomas; Korte, Wolfgang; Escher, Robert; Husmann, Marc; Blondon, Marc; Kucher, Nils (Thrombosis and Haemostasis, 2020)
Objective In patients with cancer-associated venous thromboembolism (VTE), the risk of recurrence is similar after incidental and symptomatic events. It is unknown whether the same applies to incidental VTE not associated with cancer.Methods and Results We compared baseline characteristics, anticoagulation therapy, all-cause mortality, and VTE recurrence rates at 90 days between patients with incidental (n = 131; 52% without cancer) and symptomatic (n = 1,931) VTE included in the SWIss Venous ThromboEmbolism Registry (SWIVTER). After incidental VTE, 114 (87%) patients received anticoagulation therapy for at least 3 months. The mortality rate was 9.2% after incidental and 8.4% after symptomatic VTE for hazard ratio (HR) 1.10 (95% confidence interval [CI] 0.49–2.50). After adjustment for competing risk of death, recurrence rate was 3.1 versus 2.8%, respectively, for sub-HR 1.07 (95% CI 0.39–2.93). These results were consistent among cancer (mortality: 15.9% vs. 12.6%; HR 1.32, 95% CI 0.67–2.59; recurrence: 4.8% vs. 4.7%; HR 1.02, 95% CI 0.30–3.42) and noncancer patients (mortality: 2.9% vs. 2.1%; HR 1.37, 95% CI 0.33–5.73; recurrence: 1.5% vs. 2.3%; HR 0.63, 95% CI 0.09–4.58). Patients with incidental VTE who received anticoagulation therapy for at least 3 months had lower mortality (4% vs. 41%) and recurrence rate (1% vs. 18%) compared with those who did not.Conclusion In SWIVTER, more than half of incidental VTE events occurred in noncancer patients who often received anticoagulation therapy. Among noncancer patients, early mortality and recurrence rates were similar after incidental versus symptomatic VTE. Our findings suggest that anticoagulation therapy for incidental VTE may be beneficial regardless of the presence of cancer.
Keywords: anticoagulation; incidental diagnosis; mortality; venous thromboembolism